(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Nebivolol hydrochloride (NEB) is third generation beta‑blocker, approved by the FDA to treat a hypertension. It’s a racemic mixture of a d‑Nebivolol and l‑Nebivolol. Oral delivery of the NEB shows a lower bioavailability due to its poor solubility and permeability. In present study, self nano emulsifying drug delivery is formulated to increase the bioavailability of drug by increasing solubility and permeability through the gastro intestinal membrane. Excipients are selected on basis of results obtained from solubility studies of drug in various surfactants and oils. Selected system of oil, surfactant and co‑surfactant were screened for their miscibility and emulsification ability. The ternary phase diagram was constructed using system Capmul MCM EP as oil, Tween‑60 as surfactant, Transcutol HP and PEG‑400 as co‑surfactant. Five compositions were prepared from the self‑emulsifying area of the ternary diagram, loaded with NEB and then tested for robustness to dilution, pH effect on globule size, mean globule size and polydispersity index (PDI), zeta potential, viscosity and drug release for the selection of optimized formulation. Further, the effect of viscosity and pH on the globule size and PDI of optimized SNEDDS was studied. In‑vitro drug release study was performed using dialysis bag method. Ex‑vivo drug release studies were also carried out to determine the permeability of drug loaded SNEDDS through the stomach and intestinal membrane. The optimum concentration of a system determined Capmul MCM EP 25%, Tween‑60 50%, Transcutol HP 12.5%, PEG‑400 12.5% with a globule size of 124.5 nm, cloud point at 770C and zeta potential of ‑5.123 mV. In‑vitro drug release study and ex‑vivo permeation study showed significant increase in dissolution rate and permeability respectively, as compared to the drug suspension and marketed preparation (NEBISTAR™). Key words: Dissolution, ex‑vivo drug release, nebivolol hydrochloride, self‑nanoemulsifying drug delivery systems, solubility studies